The History and Dynamics of Pondok Modern Darussalam Gontor: From Tradition to A Modern Islamic Educational Institution in Indonesia - F. Fachrurrozi; Abdul Rosyid Teguhdin Hamid (Manunggal Halim Jaya, 2026)
This study critically and historically examines the development of Pondok Modern Darussalam Gontor (PMDG), from its traditional roots in the eighteenth-century Tegalsari pesantren to its transformation into an influential modern Islamic educational institution in Indonesia. This inquiry is important because Gontor is frequently cited as a model of pesantren modernization, yet studies of its institutional dynamics, encompassing its history, educational philosophy, curriculum, and waqf-based governance, remain fragmented and have rarely been synthesized within a single analytical framework. This study employs a qualitative library-research design using a historical, descriptive, and analytical approach. It draws on primary sources in the form of institutional documents and secondary sources including accredited journal articles and reference books on Gontor. The findings show that Gontor's transformation from a traditional pesantren into a modern Islamic educational institution rests on four main pillars: first, the integration of religious and general sciences through the Kulliyatul Mu'allimin al-Islamiyah (KMI) curriculum; second, the internalization of the Panca Jiwa philosophy (sincerity, simplicity, self-reliance, Islamic brotherhood, and freedom) as a value foundation that preserves the pesantren's character amid modernization; third, innovation in institutional governance through the endowment (waqf) of the pesantren to the Muslim community in 1958, which safeguards institutional continuity across generations; and fourth, an emphasis on leadership development and an alumni network (IKPM) that has extended Gontor's influence throughout Indonesia and abroad. This study argues that the modernization initiated by Gontor's three founders did not constitute a break with tradition; rather, it represented a creative reformulation of pesantren tradition to meet contemporary challenges without losing its Islamic identity. The study recommends further comparative research to examine the replicability of the Gontor model in other pesantren across Indonesia.